2006
DOI: 10.4049/jimmunol.177.7.4709
|View full text |Cite
|
Sign up to set email alerts
|

High Vaccine Efficacy against Shigellosis of Recombinant Noninvasive Shigella Mutant That Expresses Yersinia Invasin

Abstract: Live attenuated Shigella vaccines elicit protective immune responses, but involve a potential risk of inducing a strong inflammatory reaction. The bacterial invasiveness that is crucial for Ag delivery causes inflammatory destruction of infected epithelial cells and proinflammatory cell death of infected macrophages. In this study, the noninvasive Shigella mutant ΔipaB was equipped with Yersinia invasin protein, which has been shown to mediate bacterial invasion and targeting to M cells located in follicle-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…The Shigella Δ ipaB /Inv strain has a compromised T3SS secretion, though it is internalized due to the expression of the Yersinia invasin protein (Isberg et al , 1987). Once inside cells, this mutant is unable to escape the internalization vacuole and does not replicate (Suzuki et al , 2006). Interestingly, we observed that primary infection with this mutant strain did not compromise re‐infection, which was comparable to that observed in mock‐treated cells (Figs 6B and C, and EV4A).…”
Section: Resultsmentioning
confidence: 99%
“…The Shigella Δ ipaB /Inv strain has a compromised T3SS secretion, though it is internalized due to the expression of the Yersinia invasin protein (Isberg et al , 1987). Once inside cells, this mutant is unable to escape the internalization vacuole and does not replicate (Suzuki et al , 2006). Interestingly, we observed that primary infection with this mutant strain did not compromise re‐infection, which was comparable to that observed in mock‐treated cells (Figs 6B and C, and EV4A).…”
Section: Resultsmentioning
confidence: 99%
“…A noninvasive Shigella strain with a mutation in ipaB was complemented with inv, an invasin gene of Yersinia (⌬ipaB inv strain). This rendered the ⌬ipaB inv strain invasion competent and immunogenic, yet it remained confined to the phagosome and did not induce clinically evident pathology in an animal model (140). As a result, it provides a very attractive alternative to virG mutant vaccine strains as well as a generally interesting paradigm for developing vaccines against intracellular pathogens.…”
Section: T3ss Mutants As Vaccine Strainsmentioning
confidence: 99%
“…To address the residual pathology associated with virG mutant strains while still eliciting an immune response protective against an intracellular pathogen, an alternative strategy was developed by Suzuki et al (140). A noninvasive Shigella strain with a mutation in ipaB was complemented with inv, an invasin gene of Yersinia (⌬ipaB inv strain).…”
Section: T3ss Mutants As Vaccine Strainsmentioning
confidence: 99%
“…This model is the only available animal model in rodents to study both innate and adaptive immune responses to Shigella infection, and therefore, has been largely used so far (6)(7)(8)(9)(10)(11). Induction of the inflammatory process requires fully invasive Shigella, carrying the virulence plasmid encoding the virulence effectors mandatory for the invasive/proinflammatory phenotype.…”
mentioning
confidence: 99%